Identification of the Crucial Role of CCL22 in F. nucleatum-Related Colorectal Tumorigenesis that Correlates With Tumor Microenvironment and Immune Checkpoint Therapy - Wang, Hufei; Luo, Kangjia; Guan, Zilong; Li, Zhi; Xiang, Jun; Ou, Suwen; Tao, Yangbao; Ran, Songlin; Ye, Jinhua; Ma, Tianyi; Qiao, Tianyu; Zhang, Zhiming; et al. (Frontiers in Genetics, 2022)
Colorectal cancer (CRC) is the third most common malignant cancer worldwide with the second highest mortality. Gut microbiota can educate the tumor microenvironment (TME), consequently influencing the efficacy of immune checkpoint inhibitors (ICIs). F. nucleatum is one of the most crucial bacteria contributing to colorectal tumorigenesis, but the molecular mechanisms between F. nucleatum and TME or ICIs are poorly investigated. In present study, we firstly found CCL22 mRNA expression was markedly upregulated after F. nucleatum infection. Moreover, survival analysis showed that CCL22 was significantly associated with overall survival (OS) of CRC patients. GO and KEGG analysis suggested that CCL22 was related to immune-related terms. Furthermore, ESTIMATE analysis indicated that high CCL22 expression subgroup had higher immune/stromal/estimate score, and lower tumor purity. CIBERSORT analysis indicated that high CCL22 expression group had more immune suppressive cells, and less antitumor immune cells. In addition, immune checkpoint genes and cytotoxic genes were positively correlated with CCL22 expression. An Immunophenoscore (IPS) analysis suggested that CCL22 was associated with IPS-CTLA4 and PD1/PD-L1/PD-L2 score. Interestingly, CCL22 expression in the KRAS and APC mutation groups was markedly reduced compared to wild groups. In summary, our study provided evidences that CCL22 might play a crucial role in F. nucleatum-related colorectal tumorigenesis, and correlate with TME and ICIs, which deserved further study.